A THE USE OF PARTIAL LEAST SQUARES MODELING IN FINANCE BUSINESS PARTNERING RESEARCH - Amin Tohari; Faisol Faisol; aeri rahmad (Universitas Trunojoyo Madura, 2021)
Structural equation modeling (SEM) is a set of statistical techniques that allows testing a model that is built between one or more endogenous variables with one or more exogenous variables, where each endogenous and exogenous variable can be in the form of latent or a construct built from several variables of manifest or indicator. There is Structural Equation Modeling (SEM) based on covariance and variance, known as Partial Least Square (PLS), SEM-PLS is a powerful and flexible analysis method. This research discusses about the application of SEM-PLS in the field of managerial accounting system, namely the application of non-financial performance’s role that delivers the sustainability of the company's financial performance. Based on the results obtained, it can be concluded that partial least squares can be used to model finance business partnering, and it is known that employee performance and internal process performance contribute to achieve the firm’s financial performance.